Comparative advantage or economic policy? Stylized facts and reflections on Brazil's insertion in the world economy: 1994-2005 - Armando Castelar Pinheiro; Régis Bonelli (Institute for Applied Economic Research (ipea), 2015)
This paper analyzes export performance in Brazil, discussing the roles played by export diversification, productivity enhancements, policy, and natural resource endowments. First, we provide a brief account of Brazil's recent export performance and analyze changes in the competitiveness of Brazilian exports in a long-term perspective. This is done by evaluating actual sector export patterns vis-à-vis the rest of the world in an attempt to grasp a broad picture of comparative export behavior. We proceed to evaluate changes in exports competitiveness as described by shifts in the country's revealed export behavior compared to the rest of the world, for which we rely on a traditional Constant-Market-Share (CMS) decomposition and on an extension of Hummels and Klenow's approach. Next, we analyze agricultural exports, a discussion followed by an evaluation of the role of trade policy, and in particular export promotion instruments and institutions. Among the conclusions we highlight that there are several commonalities between the present and previous export booms, in the sense that: a) it reinforced the country's diversified trade relations, with additional exports concentrated in non-traditional markets such as China, Russia, Africa, and South and Central American, non-Mercosur member countries; b) it did not change the relative share of manufactures in Brazil's export basket, despite the excellent performance of agro-based exports since the early 1990s; and c) both agricultural and manufacture exports have experienced an increasing product diversification. Yet, innovations, defined as new goods entering the export basket, were relatively unimportant, except for some specific markets.
Keywords: F14; O12; 330